The man in the middle : Conversation of a tempted soul with two voices on the seven deadly sins - Stoney, George C.; AFI/Triangle Laboratories Estate Collection (Library of Congress) (United States : [s.n.], 1968)
Through application of basic behavioral principles, police attempt to build and maintain good community relations in South Jamaica, New York, an area largely populated by racial minorities. The possible misunderstandings that can occur between local individuals and police in the routine patrol situations are analyzed as police are trained to deal with conflicting pressures.
Copyright: reg. unknown.
Sources used: NICEM Index to 16mm educational films, vol. III, 1980, p. 388; Educational film/video locator, 3rd ed., 1986, vol. ii, p. 1937.
Includes scenes shot in Berkeley, California.
Keywords: Police-community relations -- Jamaica (New York, N.Y.); Documentary films; Nonfiction films; Short films